Reformulation of Absolute Judicial Review Authority in the Constitutional Court to Uphold the Principle of Constitutional Supremacy - Hidayat, Rivan; Adiba, Ritika Sahzana (Universitas Muhammadiyah Surakarta, 2023)
The Constitutional Court and the Supreme Court's dual-roof judicial review authority has generated new legal complications. The decisions between the Supreme Court and the Constitutional Court often conflict, giving rise to legal uncertainty for justice seekers. Even though judicial review has an important role as an effort to protect the constitutional rights of citizens who are disadvantaged over the existence of norms of legislation established by the government. Through the judicial review mechanism, there is a mechanism to rectify the norms of laws and regulations to comply with the basic legal norms, namely the Constitution. However, the practice of judicial review so far in Indonesia seems ineffective because of the two-roof design at the Supreme Court and the Court. Therefore, reforming judicial review under one roof of the Constitutional Court is an alternative idea to find ways to solve existing problems. This article attempts to provide insight into the model of judicial review in Indonesia and the reformulation of judicial review authority under one roof of the Supreme Court of Justice to uphold the principle of constitutional supremacy. The study employed normative legal research methods. This study offers a reformulation of judicial review authority under one roof of the Constitutional Court. The results of this study reveal that the authority of judicial review under the two roofs of the Supreme Court and the Court has given rise to legal problems, such as conflicting decisions, which result in legal uncertainty. Ultimately, this article provides an alternative idea, namely the reformulation of judicial review authority under one roof of the Constitutional Court to create legal certainty and uphold the principle of constitutional supremacy.